PENGARUH KETELADANAN GURU PAI TERHADAP SIKAP BERBUSANA ISLAMI SISWI KELAS X DI SMA MUHAMMADIYAH 4 PALEMBANG - Laila Rahmi Hasanah; Lailatul Mukjizat; Asiana; Mona Alyaa Sausan; Febriyanti; Kurratul Aini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the level of Islamic Religious Education teachers' role models, the level of Islamic dress implementation among female students, and to examine the influence of Islamic Religious Education teachers' role models on the Islamic dress attitudes of class X female students at SMA Muhammadiyah 4 Palembang. The research method used is quantitative with a descriptive-associative approach. The research sample consisted of 23 female students determined using a purposive sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability, then analyzed using a simple linear regression test with the help of SPSS 25. The results of the study showed that: (1) The Islamic Religious Education teachers' role models were in the "Good" category (48%); (2) The Islamic dress attitudes of female students were in the "Enough" category (43%); (3) There was a positive and significant influence between the Islamic Religious Education teachers' role models on the Islamic dress attitudes of female students with a correlation coefficient (r) of 0.780 (strong correlation) and a significance value of 0.000 <0.05. The contribution of Islamic Religious Education (PAI) teacher role models to female students' dress code was 60.9%, while the remaining 39.1% was influenced by other factors such as social media exposure, peer group environment, and family background. This study concludes that teacher role models are key to the internalization of moral values ​​in schools.